20m+12=30m-18

Simple and best practice solution for 20m+12=30m-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20m+12=30m-18 equation:


Simplifying
20m + 12 = 30m + -18

Reorder the terms:
12 + 20m = 30m + -18

Reorder the terms:
12 + 20m = -18 + 30m

Solving
12 + 20m = -18 + 30m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-30m' to each side of the equation.
12 + 20m + -30m = -18 + 30m + -30m

Combine like terms: 20m + -30m = -10m
12 + -10m = -18 + 30m + -30m

Combine like terms: 30m + -30m = 0
12 + -10m = -18 + 0
12 + -10m = -18

Add '-12' to each side of the equation.
12 + -12 + -10m = -18 + -12

Combine like terms: 12 + -12 = 0
0 + -10m = -18 + -12
-10m = -18 + -12

Combine like terms: -18 + -12 = -30
-10m = -30

Divide each side by '-10'.
m = 3

Simplifying
m = 3

See similar equations:

| -2p+6-8p+9= | | 9-5c=12-(6c-7) | | 9(x-3)=63 | | 4+6x-4=3x | | 8=-12+5n | | 3y(y-2)-2y(y-3)=4 | | 500=35-4x | | 4z+5=6z+7 | | -3[w+5]+5w=2[w-6] | | 8+5x=-27 | | -9f+2+8-5f= | | 6-s=18 | | [(2x+1)-5(x-4)]+4=10(x+3) | | 5h-(8+7h)= | | 2(4e)=40 | | 1=3(k+8) | | 5-7f+8f-3= | | 13=z+5 | | 6w+5=29 | | -9-1.1x=6.8 | | x+4x-21= | | (4x-23)+(2x+17)=180 | | -6x-2x+13=-11 | | 3[x+2]+2x=7[x-1]+9 | | 5+0.1Q=20-0.2Q | | 2(4e)=35 | | 2=11-20 | | 3n^2-6n+8=0 | | 2y=37 | | 8y-6y-3=17 | | 6-18p= | | -5+8s-7+3s= |

Equations solver categories